The effectiveness of the learning cycle strategy to develop the capabilities of art education students in the subject of teaching methods (Al-Academy, 2025)
Since the current research seeks to reveal the effectiveness of the learning cycle strategy to develop the capabilities of art education students in the teaching methods subject, this research tends to the experimental method, as it is the most appropriate scientific method to achieve the research goal.The experimental design with two equivalent samples with two tests (pre-post) was chosen by exposing them to a pre- and post-test to measure the research variables (learning cycle strategy - cognitive and skill achievement). A random sample of third grade students / Art Education Department - morning study was selected, amounting to (40) male and female students who were selected from grades (A-D). The research tools were applied to them. For the purpose of extracting the results, the statistical package (SPSS) was used to process the data obtained by the researcher after applying the research procedures to the basic sample.The most important results are: It appeared that the calculated value of the cognitive achievement test amounted to (2,317), which is greater than the tabular value of (2,021) at a significance level of (0.05) in favor of the students of the experimental group who learned the teaching methods subject according to the learning cycle strategy